Respostas
respondido por:
1
a) 9 x ao quadrado + 6x + 1
b) 15 x ao quadrado - 21 + 10 - 14
15 x ao quadrado + 10 - 7
15 x ao quadrado + 3
c) 4 x ao quadrado + 2xy +9y ao quadrado
b) 15 x ao quadrado - 21 + 10 - 14
15 x ao quadrado + 10 - 7
15 x ao quadrado + 3
c) 4 x ao quadrado + 2xy +9y ao quadrado
Dereck1001:
Muito obrigado!
respondido por:
1
a)
= (3x+1)²
= (3x)² + 2.1.3x + 1
= 9x² + 6x + 1
b)
= (3x + 2).(5x - 7)
= 3x.5x - 7.3x + 2.5x + 2.(-7)
= 15x² - 21x + 10x - 14
= 15x² - 11x - 14
c)
= (2x + 3y)²
= (2x)² + 2.2x.3y + (3y)²
= 4x² + 12xy + 9y²
= (3x+1)²
= (3x)² + 2.1.3x + 1
= 9x² + 6x + 1
b)
= (3x + 2).(5x - 7)
= 3x.5x - 7.3x + 2.5x + 2.(-7)
= 15x² - 21x + 10x - 14
= 15x² - 11x - 14
c)
= (2x + 3y)²
= (2x)² + 2.2x.3y + (3y)²
= 4x² + 12xy + 9y²
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás